ESR1, ERBB2, and Ki67 mRNA expression predicts stage and grade of non-muscle-invasive bladder carcinoma (NMIBC) - Breyer, Johannes; Erben, Philipp; Kriegmair, Maximilian (Virchows Archiv, 2016)
Pathological staging and grading are crucial for risk assessment in non-muscle-invasive bladder cancer (NMIBC). Molecular grading might support pathological evaluation and minimize interobserver variability. In this study, the well-established breast cancer markers ESR1, PGR, ERBB2, and MKI67 were evaluated as potential molecular markers to support grading and staging in NMIBC. We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with NMIBC. Messenger RNA (mRNA) expression of the aforementioned markers was measured by single-step reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) using RNA-specific TaqMan assays. Relative gene expression was determined by normalization to two reference genes (CALM2 and B2M) using the 40−ΔΔCT method and correlated to histopathological stage and grade. Pathological assessment was performed by an experienced uropathologist. Statistical analysis was performed using the SAS software JMP 9.0.0 version and GraphPad Prism 5.04. Of 381 cases of NMIBC, samples of 100 pTa and 255 pT1 cases were included in the final study. Spearman rank correlation revealed significant correlations between grade and expression of MKI67 (r = 0.52, p < 0.0001), ESR1 (r = 0.25, p < 0.0001), and ERBB2 (r = 0.18, p = 0.0008). In Mann-Whitney tests, MKI67 was significantly different between all grades (p < 0.0001), while ESR1 (p = 0.0006) and ERBB2 (p = 0.027) were significantly different between G2 and G3. Higher expression of MKI67 (r = 0.49; p < 0.0001), ERBB2 (r = 0.22; p < 0.0001), and ESR1 (r = 0.18; p = 0.0009) mRNA was positively correlated with higher stage. MKI67 (p < 0.0001), ERBB2 (p = 0.0058), and PGR (p = 0.0007) were significantly different between pTa and pT1. In NMIBC expression of ESR1, ERBB2 and MKI67 are significantly different between stage and grade. This potentially provides objective parameters for pathological evaluation.
Gesehen am 31.10.2019